The school environment and its impact on the teaching-learning process in educational institutions - Ana María Velásquez Saldarriaga,; José Alberto Vigueras Moreno, (International Journal of Psychosocial Rehabilitation, 2020)
The research was directed to the study of the school environment in reference to internal and external factors, mainly constituted by abandonment, lack of values and violence, which significantly influence the success or failure of the educational process, in effect, the scientific literature determines that performance comes from socio-economic, cultural, pedagogical and technological conditions. In short, working in the spaces where activities are carried out plays a transcendental role in emotional, physical and procedural elements of the student, for this reason, the objective focused on analyzing the school environment and its impact on the teaching-learning process in educational institutions, to provide a safe and peaceful environment, where coexistence is the basis of interpersonal relationships between members of the training community, in other words, allows guiding teaching work effectively, efficiently and creatively. Certainly, the investigation was based on a qualitative approach, through unstructured observation, applying bibliographic review methods, deductive-inductive, which established the real situation of students in rural institutions; In summary, the results obtained showed high levels of bullying, demotivation and intra-family problems, in other words, it provided data on difficulties due to limitations of didactic, technological and human resources, in short, the aspect is not considered within educational reforms and ignorance causes conflicts in the pedagogical field.